Altered lower leg muscle activation patterns in patients with cerebral palsy during cycling on an ergometer - Alves-Pinto A; Blumenstein T; Turova V; Lampe R (Neuropsychiatric Disease and Treatment, 2016)
Ana Alves-Pinto,1,* Tobias Blumenstein,1,* Varvara Turova,1 Renée Lampe1,2 1Research Unit of the Buhl-Strohmaier Foundation for Cerebral Palsy and Paediatric Neuroorthopaedics, Orthopaedic Department, Klinikum rechts der Isar, 2Markus Würth Professorship, Technical University of Munich, Munich, Germany *These authors contributed equally to this work Objective: Cycling on a recumbent ergometer constitutes one of the most popular rehabilitation exercises in cerebral palsy (CP). However, no control is performed on how muscles are being used during training. Given that patients with CP present altered muscular activity patterns during cycling or walking, it is possible that an incorrect pattern of muscle activation is being promoted during rehabilitation cycling. This study investigated patterns of muscular activation during cycling on a recumbent ergometer in patients with CP and whether those patterns are determined by the degree of spasticity and of mobility.Methods: Electromyographic (EMG) recordings of lower leg muscle activation during cycling on a recumbent ergometer were performed in 14 adult patients diagnosed with CP and five adult healthy participants. EMG recordings were done with an eight-channel EMG system built in the laboratory. The activity of the following muscles was recorded: Musculus rectus femoris, Musculus biceps femoris, Musculus tibialis anterior, and Musculus gastrocnemius. The degree of muscle spasticity and mobility was assessed using the Modified Ashworth Scale and the Gross Motor Function Classification System, respectively. Muscle activation patterns were described in terms of onset and duration of activation as well as duration of cocontractions.Results: Muscle activation in CP was characterized by earlier onsets, longer periods of activation, a higher occurrence of agonist–antagonist cocontractions, and a more variable cycling tempo in comparison to healthy participants. The degree of altered muscle activation pattern correlated significantly with the degree of spasticity.Conclusion: This study confirmed the occurrence of altered lower leg muscle activation patterns in patients with CP during cycling on a recumbent ergometer. There is a need to develop feedback systems that can inform patients and therapists of an incorrect muscle activation during cycling and support the training of a more physiological activation pattern. Keywords: electromyography, rehabilitation, cocontraction, spasticity, mobility